Reformas a la ley orgánica de transporte terrestre tránsito y seguridad vial, respecto a la cobertura del seguro obligatorio de accidentes de tránsito - Bernal Perlaza, Sandra Del Rocío (2014)
The Ecuador according to data provided by international organizations such as the World Health Organization, is one of the countries with the highest rate of traffic accidents in Latin America and the world, leading to the existence of many both fatalities, as you injured as a result of such mishaps. Traffic accidents threaten fundamental human rights such as life and personal integrity, which are recognized in the Constitution of the Republic of Ecuador, which incorporates protection as a right to legal certainty, manifested through the existence of legal, clear, and previous public standards that can be applied by the competent authorities to protect the rights of citizens. Despite the high incidence of traffic accidents, and the constitutional requirement that legal rules are clear and sufficient to revise the Law on Land Transport, Traffic and Road Safety, and General Application Regulations, in relation to the Compulsory Insurance for traffic Accidents (SOAT), specifically what to do with the amount of coverage that it provides to victims of traffic accidents, which are not sufficient given the current socio-economic conditions of Ecuadorian society. We have also identified problems related to the distribution of resources allocated to the Road Accident Fund (FONSAT), as insufficient to items related to accident prevention and education in road safety funds are allocated. To study this problem earlier runs research entitled: "ORGANIC AMENDMENTS TO THE LAW OF LAND TRANSPORT SAFETY AND ROAD TRAFFIC, AS TO THE COMPULSORY INSURANCE COVERAGE OF TRAFFIC ACCIDENTS" which has a broad conceptual support, doctrinal, legal and comparative law, as well as presenting objective findings, conclusions, recommendations and ends with the presentation of a legal proposal to amend the Basic Law of Land Transport, Traffic and Road Safety, and its General Application Regulations.